Bio-degradable osteosynthesis system in treatment of mandibular parasymphysis fractures - Salim Mujawar; A.P.Krishna; Warad NM; Sulabha A.N; Sameer Choudhari (Al Ameen Medical College, 2012)
Background: Rigid internal fixation using metal compression plates, miniplates, micro plates etc are established system in treatment of facio-maxillary trauma. Most of the time results are satisfactory and are in vague. Until recently, unfortunately these well established treatments have certain inherent disadvantages like foreign body sensation, tissue reaction, secondary infection, galvanic current reaction etc. Bio-resorbable plating system has been used in the present study in selected patients and results have found to offer better advantages than routine metal plates. Objective: This study aims to demonstrate the biocompatibility and benefits of bioresorbable plating system with surrounding soft tissue and bone. Methods: The present study uses bioresorbable polyL lactic acid (PLLA) plating system to treat the mandibular fractures. These plates were assessed for biodegradability using ultrasonographic aid for period of 1 year. Results and Conclusion: We found at end of 1 year thickness of plate changed markedly with decrease in size of plates and screws with fading of bur holes. Hence these materials are satisfactory in treatment of maxillofacial fractures offering better advantage than conventional metal plating system